2007
DOI: 10.2320/matertrans.48.538
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electromagnetic Vibration Frequency and Temperature Gradient on Grain Refinement of Pure Aluminum

Abstract: The electromagnetic vibrations are applied to grain refinement of pure aluminum (99.7 mass%) and the effects of electromagnetic vibration frequency and temperature gradient on grain refinement are investigated. As the pure aluminum melt has been subjected to electromagnetic vibrations with a frequency range from 150 to 500 Hz, crystal grain has become small with increase of vibration frequency. To the contrary, the effect of refinement has become weak at the vibration frequency more than 1 kHz and this microst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…In principle, there are three main processing parameters during EMV processing; i.e., the magnetic flux density of the static magnetic field, B 0 , the effective electric current, J e , and the frequency of the alternating current, f. More often than not, the influence of vibration frequency has been investigated in a number of alloy systems [3,4,6,[8][9][10][11][12][13] and it reveals that the solidified microstructure experiences a transition, i.e., it exhibits a coarse structure at low frequency and then becomes refined at medium frequency and eventually coarsens at high frequency. Our recent investigation indicates that the AZ91D alloy [14] exhibits the similar evolution tendency in microstructure formation as a function of vibration frequency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, there are three main processing parameters during EMV processing; i.e., the magnetic flux density of the static magnetic field, B 0 , the effective electric current, J e , and the frequency of the alternating current, f. More often than not, the influence of vibration frequency has been investigated in a number of alloy systems [3,4,6,[8][9][10][11][12][13] and it reveals that the solidified microstructure experiences a transition, i.e., it exhibits a coarse structure at low frequency and then becomes refined at medium frequency and eventually coarsens at high frequency. Our recent investigation indicates that the AZ91D alloy [14] exhibits the similar evolution tendency in microstructure formation as a function of vibration frequency.…”
Section: Introductionmentioning
confidence: 99%
“…From then on, much work [3][4][5][6][7][8][9][10][11][12][13] has been preformed to examine the solidification behavior using EMV, in particular the grain refinement in various alloys [3,4,6,[8][9][10] and metals [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] In order to elucidate the origin of structure formation, cavitation due to the collapse of bubbles [2][3][4][5][6][7][8][9][10][11] is frequently referred, which is based on phenomena occurring in the ultrasonic band. As the collapse of bubbles could release shock waves, Miwa and co-workers [3][4][5][6][7][8][9][10][11] termed it as a micro-explosion mechanism that resulted in the segmentation of growing dendrites and thus refining structures. It should be noted that Vives 14) stressed the role of cavitation on refinement in the Al alloys.…”
Section: Discussionmentioning
confidence: 99%
“…They [3][4][5][6][7][8][9][10][11] found that the microstructures could be substantially refined when vibration frequency fell into a suitable interval, more often than not, within the range from about 500 Hz to less than 2000 Hz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation